Laminate, tube container body, and tube container

JP7641493B2Active Publication Date: 2025-03-07DAI NIPPON PRINTING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021026434
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-22
Publication Date
2025-03-07
Estimated Expiration
2041-02-22

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、高いリサイクル性と高い耐擦傷性とを有するチューブ容器本体を作製可能な積層体を提供できる。本発明によれば、上記積層体を備え、高いリサイクル性と高い耐擦傷性とを有する、チューブ容器本体およびチューブ容器を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641493000003
    Figure 0007641493000003
  • Figure 0007641493000004
    Figure 0007641493000004
  • Figure 0007641493000005
    Figure 0007641493000005
Patent Text Reader

Abstract

To provide a laminate capable of producing a tube container main body having high recyclability and high abrasion resistance.SOLUTION: A laminate includes: a first resin layer having heat sealability; a gas barrier resin layer; a substrate; a second resin layer having heat sealability; a printed layer; and a print protective layer in this order in a thickness direction of the laminate. The laminate includes a vapor-deposited film at least on one side of the substrate. The first resin layer, the substrate and the second resin layer are each composed of polyethylene.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate, a tube container body, and a tube container. [Background technology]

[0002] Tube containers are known as packaging containers that are filled with semi-liquid paste-like substances such as toothpaste and face wash cream and are used by squeezing them out. Tube containers usually include a tube container body and a cap. The tube container body generally includes a body portion having one end closed and the other end open, and a head portion having a spout connected to the other open end of the body portion. The body portion is filled with the contents before closing one end of the body portion, and then the one end of the body portion is closed, thereby producing a tube container containing the contents.

[0003] 2. Description of the Related Art Laminates obtained by laminating polyethylene film, polyester film, a gas barrier layer, aluminum foil, and the like are widely used as members constituting the barrel of a tube container body (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-282184 A [Patent Document 2] JP 2014-231372 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, with the growing demand for the creation of a recycling-oriented society, packaging containers are required to have high recyclability. However, as described above, the body of a conventional tube container body is composed of a laminate having layers of multiple different materials. Since it is difficult to separate the laminate into layers of different materials, it is currently difficult to recycle the tube container body. In addition, it has been found that if a highly recyclable laminate is used as a material for forming the body, the laminate has low scratch resistance, so the tube container body is easily scratched and the design may be reduced.

[0006] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a laminate that can be used to produce a tube container body that has high recyclability and high scratch resistance.

[0007] An object of the present invention is to provide a tube container body and a tube container including the above-mentioned laminate. [Means for solving the problem]

[0008] The laminate of the present invention comprises a first resin layer having heat sealability, a gas barrier resin layer, a substrate, a second resin layer having heat sealability, a printed layer, and a printed protective layer, in that order in the thickness direction of the laminate, and the laminate has a vapor deposition film on at least one surface of the substrate, and the first resin layer, the substrate, and the second resin layer are each composed of polyethylene. Effect of the Invention

[0009] According to the present invention, it is possible to provide a laminate from which a tube container body having high recyclability and high scratch resistance can be produced. According to the present invention, it is possible to provide a tube container body and a tube container comprising the above-mentioned laminate and having high recyclability and high scratch resistance. [Brief description of the drawings]

[0010] [Figure 1]FIG. 1 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. [Diagram 3] FIG. 3 is a top view of the original roll of the cylindrical body of the tube container body. [Figure 4] FIG. 4 is a perspective view showing one embodiment of a tube container comprising a tube container body including the laminate of the present invention and a cap. [Diagram 5] FIG. 5 is a cross-sectional view taken along line AA of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings. In the following description, the components (e.g., polyethylene, additives) described may be used alone or in combination of two or more.

[0012] [Laminate] The laminate of the present invention comprises a first resin layer having heat sealability, a gas barrier resin layer, a substrate, a second resin layer having heat sealability, a printed layer, and a printed protective layer, in that order in the thickness direction of the laminate, and further comprises a vapor-deposited film on at least one surface of the substrate.

[0013] One embodiment of the laminate of the present invention is shown in Fig. 1. The laminate 1 comprises a first resin layer 2 having heat sealability, a gas barrier resin layer 4, a substrate 6, a second resin layer 8 having heat sealability, a printed layer 10, and a printed protective layer 12, in this order in the thickness direction of the laminate, and further comprises a vapor-deposited film 7 on the surface of the substrate 6 facing the printed layer 10. The vapor-deposited film 7 is preferably provided on the surface of the substrate 6 facing the second resin layer 8, since this can improve the design of a tube container body produced using the laminate 1.

[0014] The first resin layer, the substrate, and the second resin layer of the laminate of the present invention are each made of the same material, polyethylene. Therefore, the laminate of the present invention has high recyclability. The tube container body including this laminate also has high recyclability.

[0015] The polyethylene content in the entire laminate of the present invention is preferably 90% by mass or more, more preferably 92% by mass or more, which can improve the recyclability of the laminate of the present invention and the tube container body including the laminate.

[0016] The laminate of the present invention has a printed layer and a printed protective layer on the outer side of the second resin layer. Therefore, the printed layer and the printed protective layer can be easily separated and removed from the laminate, and the laminate of the present invention has high recyclability. A tube container body including this laminate also has high recyclability.

[0017] The laminate of the present invention has a printed protective layer on the printed layer. This improves the scratch resistance and slipperiness of the laminate. Therefore, scratches on the conveying line during the manufacturing process of the laminate and the tube container body, on the conveying line when filling the contents into the tube container, and during transportation of the tube container can be suppressed. In addition, by providing a printed protective layer on the printed layer, a unique texture and high designability can be imparted to the laminate.

[0018] Another embodiment of the laminate of the present invention is shown in FIG. 2. The laminate 1' comprises an adhesive layer 16 between the second resin layer 8 having heat sealability and the substrate 6, a melt-extruded polyethylene layer 14 between the substrate 6 and the gas barrier resin layer 4, and a melt-extruded polyethylene layer 14 between the gas barrier resin layer 4 and the first resin layer 2 having heat sealability. The second resin layer 8 may have a multilayer structure (e.g., three resin layers). The first resin layer 2 may have a multilayer structure (e.g., three resin layers). The substrate 6 may have a multilayer structure (e.g., three resin layers). The laminate 1' includes a multi-layered gas barrier resin layer 4. The multi-layered gas barrier resin layer 4 includes a first polyethylene resin layer 4A, a first adhesive layer 4B, a layer 4C containing a gas barrier resin, a second adhesive layer 4D, and a second polyethylene resin layer 4E.

[0019] In this specification, the term "laminate" may refer to the raw roll itself produced on a production line having the above-mentioned layer structure, or may refer to each individual laminate piece obtained by cutting the raw roll, and is not particularly limited as long as it has the above-mentioned layer structure. The individual laminate pieces are used, for example, to form the body of a tube container body.

[0020] 3 shows a top view of an original web as the laminate of the present invention before being cut along cutting line L. This original web contains a plurality of continuous laminates (individual pieces) for forming the body of the tube container body. By cutting this original web along cutting line L, a plurality of laminate pieces for forming the body of the tube container body can be obtained. From the viewpoint of heat sealability, it is preferable that no printed layer or printed protective layer is formed on both ends of the laminate pieces in the direction perpendicular to the original web flow direction.

[0021] <First Resin Layer and Second Resin Layer> The first and second resin layers constituting the laminate of the present invention are each made of polyethylene and both have heat sealability. The first and second resin layers can be melted by heating and fused to each other.

[0022] When the laminate of the present invention is used to form the body of a tube container body, the first resin layer becomes a sealant layer on the inner surface side of the body, and the second resin layer becomes a sealant layer on the outer surface side of the body. That is, the body comprises, from the inside to the outside of the body, a first resin layer having heat sealability, a gas barrier resin layer, a substrate, a second resin layer having heat sealability, a printed layer, and a printed protective layer, in this order.

[0023] In the second resin layer, it is preferable that the printed layer and the printed protective layer are not formed in the area to be heat-sealed when forming the body of the tube container body. In one embodiment, the first resin layer is one surface layer of the laminate, the printed protective layer is the other surface layer of the laminate, and the second resin layer is exposed in the area to be heat-sealed.

[0024] Examples of polyethylene include high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene, and very low density polyethylene. Among these, low density polyethylene and linear low density polyethylene are preferred from the viewpoint of heat sealability.

[0025] In the present invention, the high density polyethylene has a density of 0.945 g / cm 3 For medium density polyethylene, a density of 0.926 g / cm3 is used. 3 Super 0.945g / cm 3 The following polyethylenes can be used: low density polyethylenes with a density of 0.900 g / cm 3 Super 0.926g / cm 3 The following polyethylenes can be used: linear low density polyethylene with a density of 0.900 g / cm 3 Super 0.926g / cm 3 The following polyethylenes can be used: ultra-low density polyethylene has a density of 0.900 g / cm 3 The following polyethylenes can be used:

[0026] In the present invention, the polyethylene includes a copolymer of ethylene and another monomer (hereinafter also referred to as "ethylene copolymer"). In the present invention, the content of ethylene-derived structural units in the polyethylene is preferably 30% by mass or more, more preferably 50% by mass or more, 60% by mass or more, or 70% by mass or more, and further preferably 80% by mass or more. The content can be measured, for example, by nuclear magnetic resonance (NMR).

[0027] Examples of the ethylene copolymer include copolymers of ethylene and α-olefins having 3 to 20 carbon atoms. Examples of the α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene. The polyethylene may be a copolymer of ethylene and vinyl acetate or an acrylic acid ester.

[0028] The first resin layer and the second resin layer can each independently contain a biomass-derived polyethylene obtained by polymerizing a monomer containing ethylene derived from biomass. Since such biomass-derived polyethylene is a carbon-neutral material, the environmental load in producing the laminate of the present invention can be reduced. Since biomass-derived ethylene is used as the raw material monomer, the polyethylene obtained by polymerizing the monomer is derived from biomass. The raw material monomer of the polyethylene does not have to contain 100% by mass of biomass-derived ethylene.

[0029] The raw material monomers for the biomass-derived polyethylene may further contain ethylene and / or α-olefins derived from fossil fuels, or may further contain α-olefins derived from biomass.

[0030] The concentration of ethylene derived from biomass in the polyethylene contained in the first resin layer and the second resin layer (hereinafter also referred to as "biomass ratio") is preferably 10% or more.

[0031] "Biomass ratio" is a value that measures the amount of carbon derived from biomass by radioactive carbon (C14) measurement. Carbon dioxide in the atmosphere contains a certain percentage of C14 (105.5 pMC), so it is known that the C14 content in plants that grow by absorbing carbon dioxide from the atmosphere (such as corn) is also about 105.5 pMC. It is also known that fossil fuels contain almost no C14.

[0032] Therefore, the proportion of carbon derived from biomass can be calculated by measuring the proportion of C14 in the total carbon atoms in the polyethylene. C14 The content of carbon derived from biomass, P bio It can be calculated as follows: P bio (%)=P C14 / 105.5×100

[0033] In the present invention, theoretically, if all biomass-derived ethylene is used as the raw material for polyethylene, the concentration of biomass-derived ethylene is 100%, and the biomass degree of biomass-derived polyethylene is 100%. Also, the concentration of biomass-derived ethylene in fossil fuel-derived polyethylene produced only from fossil fuel-derived raw materials is 0%, and the biomass degree of fossil fuel-derived polyethylene is 0%.

[0034] Biomass-derived ethylene can be produced using biomass-derived ethanol as a raw material. In particular, it is preferable to use biomass-derived fermented ethanol obtained from a plant raw material. As the plant raw material, a conventionally known plant can be used, for example, corn, sugarcane, beet, and manioc.

[0035] In the present invention, the fermented ethanol derived from biomass refers to ethanol produced by contacting a culture solution containing a carbon source obtained from a plant raw material with an ethanol-producing microorganism or a product derived from its crushed material, and then purifying the ethanol. Conventionally known methods such as distillation, membrane separation, and extraction can be applied to purify ethanol from the culture solution. For example, a method of adding benzene, cyclohexane, etc., and removing water by azeotropy or membrane separation can be used.

[0036] A catalyst is usually used when obtaining ethylene by the dehydration reaction of ethanol. A conventionally known catalyst can be used as the catalyst. The reaction form advantageous from the viewpoint of process is a fixed bed flow reaction, which allows easy separation of the catalyst and the product, and for example, γ-alumina is preferable.

[0037] Since this dehydration reaction is an endothermic reaction, it is usually carried out under heating conditions. As long as the reaction proceeds at a commercially useful reaction rate, the heating temperature is not particularly limited, but is preferably 100°C or higher, more preferably 250°C or higher, and even more preferably 300°C or higher. There is no particular upper limit, but from the viewpoint of energy balance and equipment, it is preferably 500°C or lower, more preferably 400°C or lower.

[0038] The reaction pressure is not particularly limited, but is preferably equal to or higher than atmospheric pressure in order to facilitate the subsequent gas-liquid separation. From an industrial perspective, a fixed bed flow reaction is preferred because it is easy to separate the catalyst, but a liquid phase suspension bed, a fluidized bed, or the like may also be used.

[0039] In the dehydration reaction of ethanol, the yield of the reaction depends on the amount of water contained in the ethanol supplied as a raw material. In general, when performing a dehydration reaction, it is preferable to have no water in consideration of the efficiency of removing water. However, in the case of the dehydration reaction of ethanol using a solid catalyst, it has been found that the amount of other olefins, especially butene, produced tends to increase in the absence of water. This is presumably because the ethylene dimerization after dehydration cannot be suppressed without the presence of a small amount of water. The lower limit of the allowable water content is preferably 0.1% by mass, more preferably 0.5% by mass. The upper limit of the allowable water content is not particularly limited, but is preferably 50% by mass, more preferably 30% by mass, and even more preferably 20% by mass from the viewpoints of material balance and heat balance.

[0040] By carrying out the dehydration reaction of ethanol in this manner, a mixture of ethylene, water, and a small amount of unreacted ethanol is obtained. Since ethylene is a gas at room temperature under about 5 MPa or less, water and ethanol can be removed from this mixture by gas-liquid separation to obtain ethylene. This method may be carried out by a known method.

[0041] The ethylene obtained by the gas-liquid separation is further distilled. The distillation method, operation temperature, residence time, etc. are not particularly limited, except that the operation pressure is normal pressure or higher.

[0042] When the raw material is biomass-derived ethanol, the resulting ethylene contains extremely small amounts of carbonyl compounds such as ketones, aldehydes, and esters, which are impurities mixed in during the ethanol fermentation process, as well as carbon dioxide, which is a decomposition product thereof, and nitrogen-containing compounds such as amines and amino acids, which are enzyme decomposition products and impurities, as well as ammonia, which is a decomposition product thereof. Depending on the use of ethylene, these extremely small amounts of impurities may be problematic, so the impurities may be removed by purification. Purification can be performed by a conventionally known method. An example of a suitable purification operation is an adsorption purification method. As the adsorbent used in this method, a conventionally known adsorbent can be used. For example, a material with a high surface area is preferable, and the type of adsorbent is selected according to the type and amount of impurities in the ethylene obtained by the dehydration reaction of biomass-derived ethanol.

[0043] As a method for purifying impurities in ethylene, a caustic water treatment may be used in combination. When the caustic water treatment is used, it is preferable to carry out the treatment before the adsorption purification. In that case, it is necessary to carry out a water removal treatment after the caustic treatment and before the adsorption purification.

[0044] The first resin layer and the second resin layer may each independently contain polyethylene recycled by mechanical recycling. Mechanical recycling is a method in which recovered polyethylene films are generally crushed, washed with an alkali to remove dirt and foreign matter from the film surface, and then dried at high temperature and reduced pressure for a certain period of time to diffuse and decontaminate the contaminants remaining inside the film, removing dirt from the polyethylene film and returning it to polyethylene.

[0045] The first resin layer and the second resin layer may each independently contain additives, such as crosslinkers, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0046] In one embodiment, the first resin layer and the second resin layer each independently have a multilayer structure, for example, a structure including a layer containing medium density polyethylene, a layer containing medium density polyethylene, and a layer containing medium density polyethylene.

[0047] In one embodiment, the first resin layer and the second resin layer are each independently a film made of polyethylene. The film may be a stretched film or an unstretched film. From the viewpoint of heat sealability, the film is preferably an unstretched film.

[0048] The first resin layer and the second resin layer may each be independently subjected to a surface treatment. This can improve the adhesion between adjacent layers. Examples of the surface treatment include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals.

[0049] Anchor coat layers may be formed independently on the surfaces of the first resin layer and the second resin layer using a conventionally known anchor coat agent.

[0050] The thickness of the first resin layer and the second resin layer is preferably 30 μm or more and 150 μm or less, more preferably 50 μm or more and 120 μm or less, independently. When the thickness is 30 μm or more, the heat sealability can be further improved. When the thickness is 150 μm or less, the processability of the laminate can be improved.

[0051] In one embodiment, the first resin layer and the second resin layer can be produced independently by forming a resin composition containing at least polyethylene into a film using a T-die method, an inflation method, etc. The first resin layer and the second resin layer can be laminated, for example, via a melt-extruded polyethylene layer or an adhesive layer, which will be described later.

[0052] <Base material> The substrate is made of polyethylene.

[0053] Examples of polyethylene include high-density polyethylene, medium-density polyethylene, low-density polyethylene, linear low-density polyethylene, and very low-density polyethylene. Among these, high-density polyethylene and medium-density polyethylene are preferred from the viewpoint of the strength and heat resistance of the substrate, and medium-density polyethylene is more preferred from the viewpoint of the stretchability of the substrate.

[0054] The substrate may contain polyethylene derived from biomass. The concentration of ethylene derived from biomass (biomass degree) in the polyethylene contained in the substrate is preferably 10% or more. The substrate may also contain polyethylene recycled by mechanical recycling. The substrate may include the additives described above.

[0055] In one embodiment, the substrate has a multi-layer structure, for example, a structure including a layer made of linear low density polyethylene, a layer made of high density polyethylene, and a layer made of linear low density polyethylene.

[0056] In one embodiment, the substrate is a film made of polyethylene. The film may be a stretched film or an unstretched film.

[0057] In one embodiment, the substrate may have a surface treated as described above. This can improve adhesion to adjacent layers. In one embodiment, an anchor coat layer may be formed on the substrate surface using a conventionally known anchor coat agent.

[0058] The thickness of the substrate is preferably 10 μm or more and 100 μm or less, more preferably 20 μm or more and 70 μm or less. When the thickness of the substrate is 10 μm or more, the strength and heat resistance can be further improved. When the thickness of the substrate is 100 μm or less, the processability of the laminate can be improved.

[0059] In one embodiment, the substrate can be produced by forming a resin composition containing at least polyethylene into a film using a T-die method, an inflation method, or the like.

[0060] <Vapor deposition film> The laminate of the present invention has a vapor-deposited film on at least one surface of the substrate. This can improve the gas barrier properties of the laminate, specifically, the oxygen barrier properties and water vapor barrier properties. The vapor-deposited film is preferably provided on the surface of the substrate facing the second resin layer, since it can improve the design of the tube container body produced using the laminate of the present invention.

[0061] The vapor deposition film may be a vapor deposition film made of a metal or a vapor deposition film made of an inorganic oxide. A vapor deposition film made of a metal (hereinafter also referred to as a "metal vapor deposition film") is preferred because it can impart a glossy feel to the tube container body or the like produced using the laminate of the present invention and improve its design.

[0062] Examples of metals include aluminum, chromium, tin, nickel, copper, silver, gold, and platinum. Examples of inorganic oxides include aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide.

[0063] The surface of the deposited film is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers.

[0064] The thickness of the vapor deposition film is preferably 1 nm or more and 150 nm or less, more preferably 5 nm or more and 60 nm or less. When the thickness is 1 nm or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved, and in the case of a metal vapor deposition film, a higher gloss can be imparted. When the thickness is 150 nm or less, the occurrence of cracks in the vapor deposition film can be suppressed, and the recyclability of the laminate can be maintained.

[0065] The deposition film on the substrate can be formed by a conventional method, for example, physical vapor deposition (PVD) methods such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition (CVD) methods such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition. For example, a composite film consisting of two or more layers of deposition films of different inorganic oxides can be formed and used by using both physical vapor deposition and chemical vapor deposition in combination.

[0066] The vacuum level in the deposition chamber was 10 before oxygen was introduced. -2 ~10 -8 After oxygen is introduced, the pressure is preferably about 10 -1 ~10 -6 The pressure is preferably about mbar. The amount of oxygen introduced varies depending on the size of the deposition machine. For the oxygen to be introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas to the extent that no problems occur. The conveying speed of the substrate is, for example, 10 m / min or more and 800 m / min or less.

[0067] <Barrier coat layer> In one embodiment, the laminate of the present invention has a barrier coat layer on the substrate and below or above the vapor-deposited film, which can further improve the oxygen barrier property and water vapor barrier property of the laminate.

[0068] In one embodiment, the barrier coat layer contains a gas barrier resin. Examples of the gas barrier resin include ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile; polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6); polyester; polyurethane; and (meth)acrylic resin. Among these, polyvinyl alcohol is preferred from the viewpoint of oxygen barrier property and water vapor barrier property. When the vapor deposition film is made of an inorganic oxide, the occurrence of cracks in the vapor deposition film can be effectively suppressed by including polyvinyl alcohol in the barrier coat layer of the above embodiment.

[0069] The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more and 95% by mass or less, more preferably 75% by mass or more and 90% by mass or less. When the content is 50% by mass or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. The barrier coat layer may contain the above additives.

[0070] The thickness of the barrier coat layer is preferably 0.01 μm to 10 μm, more preferably 0.1 μm to 5 μm. When the thickness is 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. When the thickness is 10 μm or less, the recyclability of the laminate can be maintained.

[0071] The barrier coat layer can be formed, for example, by dissolving or dispersing the above-mentioned materials in water or an appropriate organic solvent, applying the obtained coating liquid, and drying it. The barrier coat layer can also be formed, for example, by applying a commercially available barrier coating agent and drying it.

[0072] In another embodiment, the barrier coat layer is a gas barrier coating film formed by subjecting a composition containing a metal alkoxide and a water-soluble polymer to a polycondensation treatment by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, etc. When the vapor deposition film is composed of an inorganic oxide, the occurrence of cracks in the vapor deposition film can be effectively suppressed by providing the barrier coat layer of the above embodiment so as to be adjacent to the vapor deposition film.

[0073] In one embodiment, the metal alkoxide is represented by the following general formula: R 1 n M(OR 2 ) m

[0074] In the formula, R 1 and R 2 are each independently an organic group having 1 to 8 carbon atoms, M is a metal atom, n is an integer of 0 or more, m is an integer of 1 or more, and n+m represents the atomic valence of M.

[0075] R 1 and R 2 Examples of the organic group represented by the formula (1) include alkyl groups having 1 to 8 carbon atoms, specifically, methyl, ethyl, n-propyl, isopropyl, n-butyl, and isobutyl groups. Examples of the metal atom M include silicon, zirconium, titanium, and aluminum.

[0076] Examples of metal alkoxides satisfying the above general formula include tetramethoxysilane (Si(OCH3)4), tetraethoxysilane (Si(OC2H5)4), tetrapropoxysilane (Si(OC3H7)4), and tetrabutoxysilane (Si(OC4H9)4).

[0077] It is preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, a known organoalkoxysilane containing an organic reactive group can be used, and an organoalkoxysilane having an epoxy group is preferable. As the organoalkoxysilane having an epoxy group, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned. It is preferable to use the silane coupling agent in an amount of 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the metal alkoxide.

[0078] As the water-soluble polymer, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer are preferred, and from the viewpoints of oxygen barrier property, water vapor barrier property, water resistance and weather resistance, it is preferred to use these in combination.

[0079] The content of the water-soluble polymer in the composition is preferably 5 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the metal alkoxide. When the content is 5 parts by mass or more, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. When the content is 500 parts by mass or less, the film formability of the composition can be further improved.

[0080] The sol-gel catalyst is preferably an acid or an amine compound. The amine compound is preferably a tertiary amine that is substantially insoluble in water and soluble in an organic solvent, such as N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferred.

[0081] The amount of the amine compound used is preferably 0.01 to 1.0 parts by mass, more preferably 0.03 to 0.3 parts by mass, relative to 100 parts by mass of the metal alkoxide. When the amount used is 0.01 parts by mass or more, the catalytic effect can be improved. When the amount used is 1.0 parts by mass or less, the thickness of the gas barrier coating film can be made uniform.

[0082] Acids are suitably used as catalysts for the sol-gel process, mainly as catalysts for hydrolysis of metal alkoxides, silane coupling agents, etc. Examples of acids include mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as acetic acid and tartaric acid.

[0083] The amount of acid used is preferably 0.001 mol or more and 0.05 mol or less per mol of the total amount of the metal alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. When the amount of acid used is 0.001 mol or more per mol of the total amount, the catalytic effect can be improved. When the amount of acid used is 0.05 mol or less per mol of the total amount, the thickness of the gas barrier coating film can be made uniform.

[0084] The composition preferably contains water in an amount of 0.1 to 100 moles, more preferably 0.8 to 2 moles, per mole of the total amount of alkoxide. When the water content is 0.1 mole or more per mole of the total amount, the oxygen barrier property and water vapor barrier property of the laminate can be further improved. When the water content is 100 moles or less per mole of the total amount, the hydrolysis reaction can be carried out quickly.

[0085] The composition may contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, and n-butanol.

[0086] The thickness of the gas barrier coating film is preferably 0.01 μm to 100 μm, more preferably 0.1 μm to 50 μm. This allows the oxygen barrier property and water vapor barrier property to be further improved while maintaining the recyclability of the laminate. In addition, when the gas barrier coating film is provided adjacent to the deposition film made of an inorganic oxide, the occurrence of cracks in the deposition film can be suppressed.

[0087] The gas barrier coating film can be formed, for example, by applying a composition containing the above-mentioned materials by a conventionally known method such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brush coating, bar coating, or applicator coating, and then subjecting the composition to a polycondensation treatment using a sol-gel method.

[0088] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and optionally a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds.

[0089] Next, for example, the composition is applied onto a substrate by the above-mentioned conventionally known method, and dried. This drying process further advances the polycondensation reaction of the metal alkoxide and the water-soluble polymer (and the silane coupling agent, if the composition contains a silane coupling agent) to form a composite polymer layer.

[0090] Finally, the composition is heated at a temperature of preferably 20° C. to 250° C., more preferably 50° C. to 220° C., for preferably 1 second to 10 minutes, thereby forming a gas barrier coating film.

[0091] <Gas barrier resin layer> The laminate of the present invention includes a gas barrier resin layer. The gas barrier resin layer contains a gas barrier resin. This can improve the oxygen barrier property and water vapor barrier property of the laminate.

[0092] The gas barrier resin layer may have a single layer structure or a multilayer structure. When the gas barrier resin layer has a multilayer structure, at least one layer thereof contains a gas barrier resin. In one embodiment, the gas barrier resin layer of the multilayer structure includes a first polyethylene resin layer, a first adhesive layer, a layer containing a gas barrier resin, a second adhesive layer, and a second polyethylene resin layer.

[0093] The adhesive layer will be described later.

[0094] Examples of the polyethylene contained in the first polyethylene resin layer and the second polyethylene resin layer include high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene, and very low density polyethylene.

[0095] The first polyethylene resin layer and the second polyethylene resin layer may each independently contain polyethylene derived from biomass. The concentration of biomass-derived ethylene in the polyethylene (biomass degree) is preferably 10% or more. The first polyethylene resin layer and the second polyethylene resin layer may each independently contain polyethylene recycled by mechanical recycling. The first polyethylene resin layer and the second polyethylene resin layer may each independently contain the additives described above.

[0096] Examples of gas barrier resins include ethylene-vinyl alcohol copolymers (EVOH), polyvinyl alcohol, polyacrylonitrile; polyamides such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6); polyesters; polyurethanes; and (meth)acrylic resins.

[0097] The gas barrier resin layer preferably contains a compatibilizer. When the gas barrier resin layer has a multi-layer structure, two or more layers may contain a compatibilizer. When the gas barrier resin layer contains a compatibilizer, the gas barrier resin contained in the gas barrier resin layer and the polyethylene contained in the substrate or the like are uniformly mixed when the tube container body produced using the laminate of the present invention is heated and melted for recycling. This makes it possible to effectively prevent the physical properties from decreasing. In addition, it is possible to effectively prevent the transparency from decreasing.

[0098] The compatibilizer may be appropriately selected from conventionally known ones and used. From the viewpoint of recyclability, however, unsaturated carboxylic acid modified polyolefin is preferable, and maleic anhydride modified polyethylene is more preferable.

[0099] The content of the compatibilizer in the entire gas barrier resin layer is preferably 5% by mass or more and 20% by mass or less. When the content is 5% by mass or more, the above-mentioned deterioration in physical properties and deterioration in transparency can be more effectively suppressed. When the content is 20% by mass or less, the moldability of the gas barrier resin layer can be improved, and the strength deterioration of the film produced using the resin obtained by recycling the laminate of the present invention can be suppressed.

[0100] The gas barrier resin layer may contain a resin other than the gas barrier resin. Examples of such resins include polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polyethylene naphthalate; (meth)acrylic resins; vinyl resins; and cellulose resins. Among these, polyethylene is preferred from the viewpoints of adhesion to the substrate and the like and recyclability of the laminate. The gas barrier resin layer may contain the above-mentioned additives.

[0101] In one embodiment, the gas barrier resin layer is a film. The film may be a stretched film or an unstretched film. From the viewpoint of the strength of the laminate, the film is preferably a stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film.

[0102] The surface of the gas barrier resin layer is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers.

[0103] When the gas barrier resin layer has a single-layer structure, the thickness is preferably 10 μm or more and 30 μm or less, more preferably 15 μm or more and 20 μm or less. When the thickness is 10 μm or more, the gas barrier property of the laminate can be further improved. When the thickness is 30 μm or less, the recyclability of the laminate can be improved.

[0104] When the gas barrier resin layer has a multi-layer structure, the thickness of the layer containing the gas barrier resin is preferably 10 μm or more and 100 μm or less, more preferably 10 μm or more and 80 μm or less. When the thickness is 10 μm or more, the gas barrier property of the laminate can be further improved. When the thickness is 100 μm or less, the recyclability of the laminate can be further improved.

[0105] In one embodiment, the gas barrier resin layer can be produced by forming a resin composition containing at least a gas barrier resin into a film using a T-die method, an inflation method, etc. The gas barrier resin layer can be laminated to a substrate or the like via a melt-extruded polyethylene layer or an adhesive layer, which will be described later.

[0106] <Melt-extruded polyethylene layer> In one embodiment, the laminate of the present invention can have a melt-extruded polyethylene layer between any layers, for example, at least one selected from between the second resin layer and the substrate, between the substrate and the gas barrier resin layer, and between the gas barrier resin layer and the first resin layer.

[0107] Examples of polyethylene contained in the melt-extruded polyethylene layer include high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene, and very low density polyethylene. Among these, low density polyethylene, linear low density polyethylene, and very low density polyethylene are preferred from the viewpoint of interlayer adhesion.

[0108] The melt-extruded polyethylene layer may contain polyethylene derived from biomass. The concentration of ethylene derived from biomass (biomass degree) in the polyethylene contained in the melt-extruded polyethylene layer is preferably 10% or more. The melt-extruded polyethylene layer may also contain polyethylene recycled by mechanical recycling. The melt extruded polyethylene layer may include the additives described above.

[0109] The thickness of the melt-extruded polyethylene layer is preferably 5 μm or more and 30 μm or less, more preferably 10 μm or more and 20 μm or less. When the thickness is 5 μm or more, the interlayer adhesion can be further improved. When the thickness is 30 μm or less, the production cost of the laminate can be reduced and the productivity can be improved.

[0110] The melt-extruded polyethylene layer can be formed, for example, by melt-extruding a resin composition containing at least polyethylene onto a substrate or the like.

[0111] <Adhesive layer> In one embodiment, the laminate of the present invention can have an adhesive layer between any layers, for example, at least one selected from between the second resin layer and the substrate, between the substrate and the gas barrier resin layer, and between the gas barrier resin layer and the first resin layer.

[0112] When the gas barrier resin layer of the laminate of the present invention has a multilayer structure, the laminate can include an adhesive layer as a layer constituting the multilayer structure, as described above.

[0113] The adhesive layer can be formed, for example, from a conventionally known adhesive. The adhesive may be a one-component curing type, a two-component curing type, or a non-curing type.

[0114] The adhesive may be a solvent-free adhesive or a solvent-based adhesive, but from the viewpoint of environmental load, a solvent-free adhesive is preferred.

[0115] Examples of solvent-free adhesives include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives. Among these, two-liquid curing urethane adhesives are preferred.

[0116] Examples of solvent-based adhesives include rubber-based adhesives, vinyl-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and olefin-based adhesives.

[0117] When the adhesive layer is provided adjacent to the aluminum vapor-deposited film, more specifically, when the laminate comprises an aluminum vapor-deposited film on a substrate and an adhesive layer is provided between the aluminum vapor-deposited film and the second resin layer, it is preferable that the adhesive layer is made of a cured product of a resin composition containing a polyester polyol and an isocyanate compound.

[0118] When forming a laminate including a vapor-deposited film, a bending load is applied to the laminate by a molding machine or the like, which may cause cracks in the aluminum vapor-deposited film. By configuring the adhesive layer as described above, it is possible to suppress the occurrence of cracks in the aluminum vapor-deposited film, and even if cracks occur, it is possible to suppress a decrease in the oxygen barrier property and water vapor barrier property (flexural load resistance).

[0119] The polyester polyol has two or more hydroxyl groups as functional groups in one molecule. The polyester polyol has, for example, a polyester structure or a polyester polyurethane structure as a main skeleton. The isocyanate compound has two or more isocyanate groups as functional groups in one molecule.

[0120] As a specific example of a resin composition (adhesive) containing a polyester polyol and an isocyanate compound, for example, the PASLIM series sold by DIC Corporation can be used.

[0121] The resin composition may further contain at least one selected from a phosphoric acid-modified compound, a plate-like inorganic compound, a coupling agent, cyclodextrin, and a cyclodextrin derivative.

[0122] The adhesive layer may contain pigments such as titanium oxide, zinc oxide and carbon black; dyes such as disperse dyes, acid dyes and cationic dyes; and additives such as antioxidants, lubricants, colorants, stabilizers, wetting agents, thickeners, coagulants, gelling agents, anti-settling agents, softeners, hardeners, plasticizers, leveling agents, ultraviolet absorbers and flame retardants. The thickness of the adhesive layer is, for example, not less than 1 μm and not more than 5 μm.

[0123] <Print layer> The laminate of the present invention includes a printed layer. The printed layer is constituted by an image. Examples of images include characters, figures, symbols, patterns, and combinations thereof.

[0124] In one embodiment, the print layer is formed using a print layer composition such as a thermoplastic resin composition, a thermosetting resin composition, or an energy ray curable resin composition, each of which contains a colorant. Specifically, the print layer contains a thermoplastic resin, a cured product of a thermosetting resin, or a cured product of an energy ray curable resin, and a colorant.

[0125] The thermoplastic resin composition includes a thermoplastic resin and a colorant. Examples of the thermoplastic resin include polyolefin, chlorinated polyolefin, polystyrene, (meth)acrylic resin, vinyl resin, acetal resin, polyester, polyurethane, polycarbonate, polyamide, polyimide, cellulose resin, petroleum resin and fluororesin. The thermoplastic resin composition may contain the above-mentioned additives.

[0126] The thermosetting resin composition is a composition that contains a thermosetting resin, a colorant, and optionally a curing agent, and is cured by heating. In one embodiment, the thermosetting resin composition is a so-called thermosetting ink.

[0127] Examples of the thermosetting resin include phenol resin, melamine resin, urea resin, epoxy resin, unsaturated polyester, thermosetting polyurethane and silicone resin; and (meth)acrylic thermosetting resin such as polyester (meth)acrylate, urethane (meth)acrylate, epoxy (meth)acrylate, polyether (meth)acrylate, polyol (meth)acrylate, melamine (meth)acrylate and triazine (meth)acrylate. Examples of the curing agent include epoxy curing agent and isocyanate curing agent. The thermosetting resin composition may contain the above-mentioned additives.

[0128] The energy ray curable resin composition is a composition that contains a compound having an energy ray curable functional group (hereinafter also referred to as "energy ray curable compound") and a colorant, and is cured by irradiation with energy rays. In one embodiment, the energy ray curable resin composition is a so-called ultraviolet ray curable ink, and is preferably a (meth)acrylic ultraviolet ray curable ink.

[0129] Examples of energy rays include electromagnetic waves such as ultraviolet rays, infrared rays, X-rays, and gamma rays; and charged particle beams such as electron beams, proton beams, and neutron beams. Among these, ultraviolet rays are preferred from the viewpoints of curing speed, availability of the irradiation source, and price. Examples of ultraviolet irradiation sources include mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, metal halides, and LEDs. The irradiation dose of ultraviolet rays is, for example, 5 mJ / cm. 2 More than 5,000mJ / cm 2 The following is the result.

[0130] Examples of the energy ray-curable functional group include ethylenically unsaturated groups such as a (meth)acryloyl group, a vinyl group, and an allyl group; as well as an epoxy group and an oxetanyl group.

[0131] The energy ray curable compound may be, for example, a compound having an ethylenically unsaturated group, preferably a compound having two or more ethylenically unsaturated groups, and more preferably a polyfunctional (meth)acrylate compound. As the polyfunctional (meth)acrylate compound, either a monomer or an oligomer may be used.

[0132] Examples of the polyfunctional (meth)acrylate monomer include bifunctional (meth)acrylate monomers such as ethylene glycol di(meth)acrylate, bisphenol A tetraethoxy di(meth)acrylate, bisphenol A tetrapropoxy di(meth)acrylate, and 1,6-hexanediol di(meth)acrylate; and trifunctional or higher (meth)acrylate monomers such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate. The number of energy ray-curable functional groups of the polyfunctional (meth)acrylate monomer is preferably 2 or more and 6 or less, more preferably 2 or more and 3 or less.

[0133] The polyfunctional (meth)acrylate monomer may have a part of its molecular skeleton modified, and for example, monomers modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, or the like can be used.

[0134] Polyfunctional (meth)acrylate oligomers include, for example, polyester (meth)acrylates, urethane (meth)acrylates, epoxy (meth)acrylates, and polyether (meth)acrylates.

[0135] When the energy ray-curable compound is an ultraviolet ray-curable compound, the energy ray-curable composition (ultraviolet ray-curable resin composition) preferably contains at least one selected from a photopolymerization initiator and a photopolymerization accelerator.

[0136] Examples of the photopolymerization initiator include acetophenones, benzophenones, thioxanthones, α-hydroxyalkylphenones, Michler's ketone, benzoin, benzil dimethyl ketal, benzoyl benzoate, and α-acyloxime ester.

[0137] The photopolymerization accelerator is a component that can reduce polymerization inhibition caused by air during curing and increase the curing speed, and examples thereof include p-dimethylaminobenzoic acid isoamyl ester and p-dimethylaminobenzoic acid ethyl ester. The energy ray-curable resin composition may contain the above-mentioned additives.

[0138] Examples of the colorant include pigments and dyes. Specific examples of the pigment include titanium oxide, zinc oxide, carbon black, iron oxide, yellow iron, ultramarine blue, metallic pigments, pearl pigments, and fluorescent pigments. The print layer may be a high-brightness layer having a high metallic luster.

[0139] The printing layer composition may contain an organic solvent or water from the viewpoint of improving the coating properties, etc. Examples of organic solvents include hydrocarbons such as toluene and xylene, ketones such as acetone and methyl ethyl ketone, esters such as ethyl acetate, cellosolve acetate, and butyl cellosolve acetate, and alcohols such as propanol.

[0140] For example, the printing layer composition can be applied onto the second resin layer and dried, followed by heating at a temperature required for curing in the case of a thermosetting resin composition, or irradiating with energy rays in the case of an energy ray curable resin composition, to form a printing layer. If the printing layer composition does not contain an organic solvent or water, drying is not necessary.

[0141] Examples of printing methods for the printing layer include letterpress printing, flexographic printing, gravure printing, offset printing, screen printing, inkjet printing, and thermal transfer printing. When the printing layer is formed by letterpress printing or flexographic printing, it is preferable to use an energy ray curable resin composition, and it is more preferable to use an ultraviolet ray curable resin composition.

[0142] In one embodiment, the printing layer includes a sublimation dye. The printing layer of this embodiment can be formed, for example, by sublimation transfer printing using a thermal transfer sheet. The thickness of the printed layer is, for example, 0.01 μm or more and 30 μm or less, preferably 0.5 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less.

[0143] <Printing protection layer> The laminate of the present invention has a printed protective layer on the printed layer, for example, to improve the scratch resistance and weather resistance of the printed layer. The laminate of the present invention preferably has a printed protective layer that covers the entire area of ​​the printed layer. From the viewpoint of visibility of the printed layer, the printed protective layer is preferably transparent in the visible light region, and more preferably colorless and transparent.

[0144] In one embodiment, the print protective layer is formed using a composition for print protective layer such as a thermoplastic resin composition, a thermosetting resin composition, and an energy ray curable resin composition. Specifically, the print layer contains a thermoplastic resin, a cured product of a thermosetting resin, or a cured product of an energy ray curable resin. Among these, from the viewpoint of improving scratch resistance and weather resistance, the print protective layer preferably contains a cured product of a thermosetting resin or a cured product of an energy ray curable resin, and more preferably contains a cured product of an energy ray curable resin. The proportion of the above cured product in the total resin components of the print protective layer is preferably 80% by mass or more, more preferably 90% by mass or more.

[0145] The thermoplastic resin composition contains a thermoplastic resin. Specific examples of the thermoplastic resin are as described above. The thermoplastic resin composition may contain the above-mentioned additives.

[0146] The thermosetting resin composition is a composition that contains a thermosetting resin and, if necessary, a curing agent, and is cured by heating. In one embodiment, the thermosetting resin composition is a so-called thermosetting varnish. Specific examples of the thermosetting resin and the curing agent are as described above. The thermosetting resin composition can contain the above-mentioned additives.

[0147] The energy ray curable resin composition is a composition that contains an energy ray curable compound, and optionally at least one selected from a photopolymerization initiator and a photopolymerization accelerator, and is cured by irradiation with energy rays. In one embodiment, the energy ray curable resin composition is a so-called ultraviolet curable varnish, and is preferably a (meth)acrylic ultraviolet curable varnish. Specific examples of the energy ray curable compound, the photopolymerization initiator, and the photopolymerization accelerator are as described above. The energy ray curable resin composition can contain the above additives.

[0148] The composition for print protective layer may contain an organic solvent or water from the viewpoint of improving the coating property, etc. Specific examples of the organic solvent are as described above.

[0149] For example, the printed protective layer can be formed by applying the composition for the printed protective layer onto the printed layer surface of the laminate precursor and drying it, followed by heating at a temperature required for curing in the case of a thermosetting resin composition, or irradiating with energy rays in the case of an energy ray curable resin composition. When the composition for the printed protective layer does not contain an organic solvent or water, drying is not necessary.

[0150] Examples of printing methods for the printed protective layer include letterpress printing, flexographic printing, gravure printing, offset printing, screen printing, inkjet printing, and thermal transfer printing. When the printed protective layer is formed by letterpress printing or flexographic printing, it is preferable to use an energy ray curable resin composition, and it is more preferable to use an ultraviolet ray curable resin composition.

[0151] The thickness of the printed protective layer is preferably 0.5 μm or more and 15 μm or less, more preferably 1 μm or more and 10 μm or less, which can improve, for example, the scratch resistance and weather resistance of the laminate.

[0152] In one embodiment, the present invention provides a laminate having a first resin layer having heat sealability, a gas barrier resin layer, a substrate, and a second resin layer having heat sealability, and a deposition film on at least one surface of the substrate. The laminate is then cut at a predetermined interval in the flow direction of the laminate. This results in a plurality of long laminates. Then, a printed layer and a printed protective layer are formed on each of the cut laminates. This method is possible because the printed layer and the printed protective layer are formed on the outermost layer side of the laminate. According to the above method, various flow dimensions and width dimensions can be accommodated, and each laminate having a printed layer can be produced in small lots. In addition, the productivity of the laminate can be improved because the laminate can be produced at high speed.

[0153] [Tube container body] The tube container body of the present invention includes the above-described laminate.

[0154] The tube container body of the present invention will be described below with reference to the drawings. Fig. 4 is a diagram showing a simplified configuration of a tube container 20, and Fig. 5 is a cross-sectional view taken along line AA in Fig. 4. As shown in Fig. 4, the tube container body 21 includes a head 22 and a body 23, and the body 23 is made of the laminate of the present invention.

[0155] <Head> The head 22 includes a shoulder 24 connected to one end of the body 23, and a spout 25 connected to the shoulder 24. In one embodiment, the spout 25 includes threads 27 for threading a cap 26 thereon.

[0156] In one embodiment, the head portion is made of a resin composition containing polyethylene. This can improve the recyclability of the tube container body. Examples of polyethylene include high-density polyethylene, medium-density polyethylene, low-density polyethylene, linear low-density polyethylene, and very low-density polyethylene. Among these, high-density polyethylene is preferred from the viewpoints of shape retention and moldability.

[0157] The resin composition may contain at least one selected from biomass-derived polyethylene and polyethylene recycled by mechanical recycling. The resin composition may contain the additives.

[0158] The head portion can be manufactured by a conventional method, for example, by compression molding or injection molding, and can be joined to the body portion.

[0159] When a tube container body is manufactured using a compression molding method, the body is attached to a male mold having a convex portion on the top, the male mold and female mold are then opposed to each other, a molten resin composition is supplied into the male and female molds, and the head is formed by compression molding, and the head is joined to one opening of the body, thereby manufacturing a tube container body having a head and a body.

[0160] When manufacturing a tube container body using an injection molding method, the body is attached to a male mold having a convex portion on the top, the male mold and female mold are then opposed to each other, a molten resin composition is supplied from a gate, and the head is formed by injection molding, and the head is joined to one opening of the body, thereby manufacturing a tube container body equipped with a head and a body.

[0161] <Torso> In the tube container body 21 of the present invention, the body 23 is connected to a shoulder 24 of the head 22. The body 23 includes a welded part 28 formed, for example, by overlapping the laminate of the present invention at one end so that the first resin layer side surface at the first end is in contact with the second resin layer side surface at the other end, rolling the laminate into a cylindrical shape, and heat-sealing the overlapped part. The body 23 includes a bottom seal part 29 formed, for example, by heat-sealing an opening of the laminate rolled into a cylindrical shape.

[0162] Examples of the heat sealing method include conventionally known methods such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing and flame sealing.

[0163] In one embodiment, the laminate of the present invention is rolled into a cylindrical shape by overlapping one end of the laminate with the second resin layer side surface of the other end of the laminate so that the first resin layer side surface is in contact with the second resin layer side surface of the other end, and the overlapped portion is heat-sealed to produce a cylindrical body. From the viewpoint of heat sealability, it is preferable that one end of the overlapping portion is the first resin layer and the other end is the second resin layer. In this case, the first resin layer and the second resin layer are melted and joined to form a welded portion.

[0164] Therefore, it is preferable that the second resin layer does not have a printed layer or a printed protective layer formed in an area to be heat sealed when forming the body of the tube container body, so that the area can be well heat sealed when forming the cylindrical body using the laminate of the present invention.

[0165] In the above, the welded portion is formed by overlapping, but the same surfaces of both ends of the laminate may be butted together and the first resin layers may be heat-sealed to join them. In this case, a printed layer and a printed protective layer may be formed on the second resin layer at both ends of the laminate. Also, in this case, a joining tape may be attached to the outer surface side of the body so as to cover the joining portion. It is preferable that a printed layer and a printed protective layer are not provided at the portion of the laminate where the joining tape is attached. The joining tape may be provided on both the inner surface and the outer surface of the body.

[0166] [Tube container] The tube container of the present invention will be described below with reference to the drawings. As shown in Fig. 4, the tube container 20 of the present invention comprises a tube container body 21 and a cap 26 attached to a head portion 22.

[0167] <Tube container body> The tube container body has been described above, so a description thereof will be omitted here.

[0168] <Cap> The cap is removably attached to the extraction port of the head and serves to close the extraction port. In one embodiment, the cap is made of a resin composition including a thermoplastic resin.

[0169] Examples of thermoplastic resins include polyolefins such as polyethylene and polypropylene; polyesters; cellulose resins; and vinyl resins. From the viewpoint of recyclability, polyethylene is particularly preferred. Examples of polyethylene include high-density polyethylene, medium-density polyethylene, low-density polyethylene, linear low-density polyethylene, and very low-density polyethylene. Among these, high-density polyethylene is preferred from the viewpoint of shape retention and opening.

[0170] The resin composition may contain at least one selected from biomass-derived polyethylene and polyethylene recycled by mechanical recycling. The resin composition may contain the additives.

[0171] The cap may be of a screw type having a groove on the inner surface thereof so as to screw into the threads 27 of the extraction port 25, as shown in FIG. 4, or it may be of a plug type which is fitted to the extraction port 25 by plugging it.

[0172] The present invention relates to, for example, the following [1] to

[17] . [1] A laminate comprising a first resin layer having heat sealability, a gas barrier resin layer, a substrate, a second resin layer having heat sealability, a printed layer, and a printed protective layer in this order in the thickness direction of the laminate, the laminate comprising a vapor deposition film on at least one surface of the substrate, and the first resin layer, the substrate, and the second resin layer are each made of polyethylene. [2] The laminate according to the above [1], wherein the printed protective layer comprises a cured product of an energy ray curable resin or a cured product of a thermosetting resin. [3] The laminate according to [1] or [2] above, further comprising a melt-extruded polyethylene layer or an adhesive layer in one or more positions selected from between the second resin layer and the substrate, between the substrate and the gas barrier resin layer, and between the gas barrier resin layer and the first resin layer. [4] The laminate according to any one of the above [1] to [3], wherein the polyethylene constituting the first resin layer and the second resin layer is each independently at least one selected from low-density polyethylene and linear low-density polyethylene. [5] The laminate according to any one of the above [1] to [4], wherein the vapor-deposited film is a metal vapor-deposited film. [6] The laminate according to any one of the above [1] to [5], wherein the first resin layer and the second resin layer each have a thickness independently of each other of 30 μm or more and 150 μm or less. [7] The laminate according to any one of the above [1] to [6], wherein the thickness of the substrate is 10 μm or more and 100 μm or less. [8] The laminate according to any one of the above [1] to [7], wherein the thickness of the vapor-deposited film is 1 nm or more and 150 nm or less. [9] The laminate according to any one of the above [1] to [8], wherein the gas barrier resin layer comprises a first polyethylene resin layer, a first adhesive layer, a layer containing a gas barrier resin, a second adhesive layer, and a second polyethylene resin layer.

[10] The laminate according to the above [9], wherein the thickness of the layer containing the gas barrier resin is 10 μm or more and 100 μm or less.

[11] The laminate according to any one of the above [1] to

[10] , wherein the polyethylene content in the entire laminate is 90 mass % or more.

[12] A laminate for forming a body of a tube container body, the laminate being described in any one of the above [1] to

[11] , wherein the first resin layer is a sealant layer on the inner surface side of the body, and the second resin layer is a sealant layer on the outer surface side of the body.

[13] The laminate according to the above

[12] , wherein in the second resin layer, a printed layer and a printed protective layer are not formed in a region intended for heat sealing to form a barrel portion of a tube container body.

[14] A tube container body having a head and a body, wherein the head has a shoulder connected to one end of the body and a spout connected to the shoulder, and the body is made of the laminate described in any one of [1] to

[13] above.

[15] The tube container body according to the above

[14] , wherein the head portion is made of a resin composition containing polyethylene.

[16] A tube container comprising the tube container body according to

[14] or

[15] above and a cap.

[17] The tube container according to

[16] above, wherein the cap is made of a resin composition containing polyethylene. EXAMPLES

[0173] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0174] [Example 1] Linear low-density polyethylene 1 (Dow Chemical, DOWLEX2098G, density 0.926 g / cm 3 ) and high-density polyethylene (ExxonMobil, HTA108, density 0.961g / cm 3 ) and linear low-density polyethylene 2 (ExxonMobil, Exceed2018HA, density 0.918g / cm 3 ) were co-extruded by an inflation method to obtain a substrate.

[0175] The substrate has a three-layer structure with a total thickness of 50 μm, comprising a 12.5 μm thick layer made of linear low-density polyethylene 1, a 25 μm thick layer made of high-density polyethylene, and a 12.5 μm thick layer made of linear low-density polyethylene 2 (linear low-density polyethylene 1 layer / high-density polyethylene layer / linear low-density polyethylene 2 layers).

[0176] On the surface of the layer made of the linear low-density polyethylene 2 in the above-mentioned substrate, an aluminum vapor deposition film having a thickness of 20 nm was formed by a PVD method.

[0177] Linear low-density polyethylene (Dow Chemical, DOWLEX2045G, density 0.920g / cm 3 ), adhesive resin (Mitsui Chemicals, Admer NF557), and ethylene-vinyl alcohol copolymer (Kuraray, EVAL H171B, density 1.17 g / cm 3 , ethylene content 38 mol%), adhesive resin (Mitsui Chemicals, Admer NF557), linear low-density polyethylene (Dow Chemical, DOWLEX2045G, density 0.920 g / cm 3 ) were co-extruded by the inflation method to form a five-layer gas barrier film.

[0178] The gas barrier film obtained as described above had a five-layer structure with a total thickness of 75 μm, including a 21.9 μm thick layer made of linear low density polyethylene, a 6.25 μm thick layer made of adhesive resin, a 18.75 μm thick layer made of ethylene-vinyl alcohol copolymer, a 6.25 μm thick layer made of adhesive resin, and a 21.9 μm thick layer made of linear low density polyethylene (linear low density polyethylene layer / adhesive resin layer / ethylene-vinyl alcohol copolymer layer / adhesive resin layer / linear low density polyethylene layer).

[0179] A low-density polyethylene (Sumitomo Chemical, Sumikathene L705, density: 0.919 g / cm) was applied onto the non-deposited film-forming surface of the substrate (linear low-density polyethylene layer). 3 ) was melt-extruded to form a melt-extruded polyethylene layer having a thickness of 15 μm, and a gas barrier film was laminated on this melt-extruded polyethylene layer.

[0180] On the laminated gas barrier film, a low-density polyethylene film (Sumitomo Chemical Co., Ltd., Sumikathene L705, density: 0.919 g / cm 3 ) was melt-extruded to form a melt-extruded polyethylene layer having a thickness of 15 μm, and a polyethylene film having a thickness of 120 μm was laminated on the melt-extruded polyethylene layer, with a mixture of DOWLEX 2038.68G manufactured by Dow Chemical and LDPE LD2420H manufactured by PTT CHEMICAL as the innermost layer, a mixture of ELITE 5538G manufactured by Dow Chemical and LDPE LD2420F manufactured by PTT CHEMICAL as the middle layer, and DOWLEX 2038.68G and AB-MB 101820-K (master batch containing 20 mass% synthetic silica-based antiblocking agent) manufactured by Dow Chemical as the outermost layer by three-layer co-extrusion as the first resin layer (innermost layer).

[0181] A urethane-based two-liquid curing adhesive (manufactured by Rock Paint, base agent: RU-004, curing agent: H-1) was applied onto the aluminum vapor deposition film and dried to form an adhesive layer with a thickness of 3 μm. At the same time, a mixture of ENABLE 2705MC manufactured by EXXON CHEMICAL, EXCEED 1327MA manufactured by EXXON CHEMICAL, and LDPE LD2420F manufactured by PTT CHEMICAL was co-extruded in three layers by the inflation method as the second resin layer through this adhesive layer. The mixture was a mixture of ENABLE 3505MC manufactured by EXXON CHEMICAL, ELITE 5860G1 manufactured by Dow Chemical, and LDPE LD2420F manufactured by PTT CHEMICAL as the innermost layer, a mixture of ENABLE 2705MC manufactured by EXXON CHEMICAL, EXCEED 1327MA manufactured by EXXON CHEMICAL, and LDPE LD2420F manufactured by PTT CHEMICAL as the middle layer, and a mixture of ENABLE 2705MC manufactured by EXXON CHEMICAL, EXCEED 1327MA manufactured by EXXON CHEMICAL, and LDPE LD2420F manufactured by PTT CHEMICAL as the outermost layer. The mixture of LD2420F was cast into a film, and a polyethylene film having a thickness of 75 μm was laminated thereon.

[0182] On the second resin layer, ultraviolet-curable ink (UV161, manufactured by T&K TOKA) was applied by letterpress printing so that the thickness after drying was 2 μm, and then it was irradiated with ultraviolet light to cure, forming a printed layer. On the surface of this printed layer, ultraviolet-curable printing varnish (Bestcure UV LTP FL OP varnish, manufactured by T&K TOKA) was applied so that the thickness after drying was 3 μm, and then it was irradiated with ultraviolet light to cure, forming a printed protective layer (outermost layer). However, the printed layer and the printed protective layer were not formed in the area corresponding to the 4.0 mm region at one end and the 2.0 mm region at the other end in the width direction (perpendicular to the flow direction of the original roll) of the laminate piece obtained by the slit processing described later.

[0183] In this manner, a laminate was obtained. The polyethylene content in this laminate was 92.4% by mass.

[0184] [Example 2] A laminate was obtained in the same manner as in Example 1, except that an ultraviolet-curable ink (UV Flexo CF, manufactured by T&K TOKA) was applied by flexographic printing onto the second resin layer so that the thickness after drying was 2 μm, and then dried and cured by irradiation with ultraviolet light to form a printed layer, and an ultraviolet-curable printing varnish (FD FL OP Varnish AQF4, manufactured by Toyo Ink Co., Ltd.) was applied onto the surface of this printed layer so that the thickness after drying was 3 μm, and then dried and cured by irradiation with ultraviolet light to form a printed protective layer. The polyethylene content in this laminate was 92.4% by mass.

[0185] [Comparative Example 1] A 12 μm-thick biaxially oriented polyethylene terephthalate (PET) film (Toyobo, E5200) was used as the substrate. A urethane-based gravure ink (Toyo Ink, NEW-LP Super) was applied to the substrate by gravure printing so that the thickness after drying was 1 μm, and then dried to form a printed layer.

[0186] A urethane-based two-component curing adhesive (manufactured by Rock Paint, base agent: RU-80, curing agent: H-5) was applied to the printed layer surface of the substrate and dried to form a 3 μm thick adhesive layer, and a 12 μm thick aluminum-deposited PET film (manufactured by Toray Film Processing Co., Ltd., BR-PET 1312) was laminated as a barrier film via this adhesive layer. The aluminum-deposited PET film was placed so that the aluminum-deposited surface faced the outermost surface.

[0187] A urethane-based two-component curing adhesive (manufactured by Rock Paint, base agent: RU-80, curing agent: H-5) was applied onto an aluminum-deposited PET film and dried to form a 3 μm-thick adhesive layer, and a 180 μm-thick linear density polyethylene film (manufactured by Prime Polymer, product name: film formed using Evolue SP2320) was laminated on top of this adhesive layer as the first resin layer.

[0188] A urethane-based two-component curing adhesive (manufactured by Rock Paint, base agent: RU-80, curing agent: H-5) was applied to the non-printing layer surface of the substrate and dried to form a 3 μm thick adhesive layer, and a 130 μm thick linear low-density polyethylene film (manufactured by Prime Polymer, product name: film produced using Evolue SP2320) was laminated on top of this adhesive layer as a second resin layer.

[0189] In this way, a laminate was obtained. The layer structure of the laminate from the innermost layer to the outermost layer was: linear low-density polyethylene film 180 μm / adhesive layer / barrier film 12 μm / adhesive layer / printed layer / biaxially oriented polyethylene terephthalate film 12 μm / adhesive layer / linear low-density polyethylene film 130 μm.

[0190] The polyethylene content in this laminate was 86.8% by mass.

[0191] [Comparative Example 2] A 12 μm-thick biaxially oriented polyethylene terephthalate (PET) film (Toyobo, E5200) was used as the substrate. A urethane-based gravure ink (Toyo Ink, NEW-LP Super) was applied to the substrate by gravure printing so that the thickness after drying was 1 μm, and then dried to form a printed layer.

[0192] A urethane-based two-component curing adhesive (manufactured by Rock Paint, base agent: RU-80, curing agent: H-5) was applied to the printed layer surface of the substrate and dried to form a 3 μm thick adhesive layer, and a 12 μm thick aluminum-deposited PET film (manufactured by Toray Film Processing, VM1310) was laminated as a barrier film via this adhesive layer. The aluminum-deposited PET film was placed so that the aluminum-deposited surface faced the outermost surface.

[0193] An anchor coating agent (Mitsui Chemicals Polyurethanes, base agent: Takelac A3210, hardener: Takenate A3075, dilution solvent: ethyl acetate) was applied onto an aluminum-deposited PET film and dried to form an anchor coating layer. Low-density polyethylene (Dow Chemicals, AGILITY EC7000) was extruded onto the anchor coating layer to form a 20 μm-thick polyethylene layer, and a 130 μm-thick linear low-density polyethylene film (Prime Polymer, a milky film formed using Evolu SP2320) was laminated through this polyethylene layer. An anchor coating agent (DICG, AC-Q.ET) was applied onto a low-density polyethylene film and dried to form an anchor coating layer. An ethylene-methacrylic acid copolymer (Mitsui DuPont Polychemical, Nucrel N0908C) was extruded onto the anchor coating layer to form a 20 μm thick adhesive layer, and an aluminum foil (Toyo Aluminum) with a thickness of 10 μm was laminated through this adhesive layer. An ethylene-methacrylic acid copolymer (Mitsui DuPont Polychemical, Nucrel N0908C) was extruded onto the barrier layer to form a 35 μm thick adhesive layer. A low-density polyethylene (Dow Chemical, AGILITY EC7000) was extruded onto the adhesive layer to form a 25 μm thick polyethylene layer, and a 25 μm thick low-density polyethylene film (Japan Polyethylene, film produced using Novatec LD LC602A) was laminated through this polyethylene layer.

[0194] An anchor coat agent (Toyo Morton, EL510 / CAT-RT80, dilution solvent: ethyl acetate) was applied to the non-printed layer surface of the substrate and dried to form an anchor coat layer, and low-density polyethylene (Dow Chemical, AGILITY EC7000) was extruded onto the anchor coat layer to form a polyethylene layer with a thickness of 25 μm, and a low-density polyethylene film with a thickness of 35 μm (Japan Polyethylene, film formed using Novatec LD LC602A) was laminated through the polyethylene layer. A print layer and a print protection layer were formed on the low-density polyethylene film in the same manner as in Example 1.

[0195] The polyethylene content in this laminate was 67.8% by mass.

[0196] [Comparative Example 3] A laminate was obtained in the same manner as in Comparative Example 2, except that the printed layer and the printed protective layer were formed in the same manner as in Example 2. The polyethylene content in this laminate was 67.8% by mass.

[0197] [Preparation of tube containers] The laminate obtained as described above was cut into a 157.3 mm wide slit using a bobbin cutter, and both ends in the width direction were overlapped so that the overlap width was about 1.2 mm, and then the overlapped ends were heat sealed to obtain a cylindrical raw roll with a tube. The obtained raw roll was cut in the length direction to 184.2 mm to produce a cylindrical body portion that would become the body portion of the tube container.

[0198] The cylindrical body was attached to a mandrel for forming a tube container, and a head portion consisting of a truncated cone-shaped shoulder portion and a cylindrical extraction port portion connected to the shoulder portion was attached to one end of the cylindrical body using a high-density polyethylene (Suntec J345, manufactured by Asahi Kasei, density 0.956 g / cm 3 ) was used for compression molding to produce a tube container body as shown in Figure 4. The spout part at the top of the obtained tube container body had an outer diameter of 30.4 mm, a height of 9.5 mm, and a thread was provided on the side of the spout part. The outer diameter of the shoulder part was 50 mm.

[0199] Next, the high density polyethylene was injected into a die for forming a cap and molded to prepare a cap, thereby obtaining a tube container.

[0200] [JSPS Examination] The outermost surface of the laminate obtained in the examples and comparative examples was set in a Gakushin tester "FR-2" (manufactured by Suga Test Instruments), and a Gakushin test was performed against a metal plate (stainless steel) and a film in accordance with JIS L-0849, with a test load of 200 gf, a reciprocating speed of 30 cpm, a stroke of 120 mm, and 300 reciprocating times. For the test against metal, the laminate was rubbed against the metal with the printed protective layer (polyethylene film in Comparative Example 1) facing up. For the test against film, the laminate was wrapped around the metal with the printed protective layer (polyethylene film in Comparative Example 1) facing up, and the printed protective layers were rubbed against each other. After the test, the condition of the outermost surface of the laminate was visually confirmed, and the scratch resistance of the outermost surface of the laminate was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 1.

[0201] AA: Extremely good BB: Good CC: Inferior

[0202] [Slipperiness test] The static and dynamic friction coefficients of the outermost layer surfaces of the laminates obtained in the examples and comparative examples were measured against a metal plate and a film (same meaning as in the Gakushin test) using a sliding tester "TR-2" (manufactured by Toyo Seiki Co., Ltd.) in accordance with JIS K7125 at a test speed of 100 mm / min. The measurement results are shown in Table 1.

[0203] [Small lot support] The processability of the laminate was evaluated in small lots (10,000 to 30,000 pieces / lot) of tube containers obtained using the laminate with a width of 157.3 mm, based on the following criteria. The evaluation results are shown in Table 1.

[0204] AA: Good (low loss rate or good processability) BB: Slightly inferior (high loss rate or poor workability) CC: Very poor (loss rate is very high or processability is very poor)

[0205] [Recyclability evaluation] The recyclability of the laminates obtained in the examples and comparative examples was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 1.

[0206] AA: The content of the same polyolefin in the laminate is 90% by mass or more, and the printed layer and the printed protective layer are located on the outermost layer side of the laminate, so that they can be easily peeled off. BB: The content of the same polyolefin in the laminate is 90% by mass or more. CC: The content of the same polyolefin in the laminate is less than 90 mass%.

[0207] [Design] A 100 mm square sample was cut out from the laminate obtained in the Examples and Comparative Examples, and the sample was placed on a desk. In a test environment with an illuminance of 400 lux (corresponding to a bright office), the design of the sample was observed from a position 500 mm above, changing the direction and angle, and evaluated according to the following criteria. The observation results of 10 observers were tabulated and averaged, and are shown in Table 1.

[0208] AA: Extremely good BB: Good CC: Inferior

[0209] [Touch] Samples of 100 mm square were cut out from the laminates obtained in the Examples and Comparative Examples, and the tactile sensations of the samples by 10 testers were collected and averaged, and the results are shown in Table 1.

[0210] AA: Extremely good BB: Good CC: Inferior

[0211] [Table 1]

[0212] It was found that the laminates of Examples 1 and 2 had better scratch resistance and better slipperiness than the laminate of Comparative Example 1. In addition, the laminates of Comparative Examples 2 and 3 contain many components other than polyethylene, and therefore are considered to have low recyclability.

[0213] [Gas permeability test] The laminates obtained in the examples and comparative examples were measured for oxygen permeability (cc / m) using an oxygen permeability measuring device (OXTRAN, manufactured by MOCON) under conditions of a temperature of 23°C and a humidity of 90% RH. 2 / day / atm) was measured.

[0214] The laminates obtained in the examples and comparative examples were measured for water vapor permeability (g / m) using a water vapor permeability tester (PERMATRAN, manufactured by MOCON) under conditions of a temperature of 40° C. and a humidity of 90% RH. 2 / day / atm) was measured.

[0215] The measurement was carried out for two sheets of each laminate, and the average value of the obtained values ​​was calculated.

[0216] [Table 2]

[0217] The gas barrier property of the laminate in Example 1 is superior to that in Comparative Example 1. Furthermore, the tubular container body obtained in the Example had good shoulder adhesive strength and side seam strength. [Explanation of symbols]

[0218] 1, 1': Laminate 2: First resin layer having heat sealability 4: Gas barrier resin layer 4A: First polyethylene resin layer 4B: First adhesive layer 4C: Layer containing gas barrier resin 4D: Second adhesive layer 4E: Second polyethylene resin layer 6: Base material 7: Evaporation film 8: Second resin layer having heat sealability 10: Printing layer 12:Printing protective layer 14: Melt-extruded polyethylene layer 16: Adhesive layer 20: Tube container 21: Tube container body 22:Head 23: Torso 24:Shoulder 25:Extraction port 26: Cap 27: Spiral 28: Welded part 29: Bottom seal

Claims

1. A laminate (excluding a laminate provided with an optical diffraction structure layer having a relief hologram or a relief pattern of a diffraction grating, or an optical diffraction structure layer having a volume hologram formed thereon), the laminate comprises, in a thickness direction of the laminate, a first resin layer having heat sealability, a gas barrier resin layer, a base material, a second resin layer having heat sealability, a printed layer, and a printed protective layer in this order; the laminate comprises a vapor-deposited film on at least one surface of the substrate, The first resin layer, the base material, and the second resin layer are each made of polyethylene. Laminate.

2. The laminate according to claim 1 , wherein the printed protective layer comprises a cured product of an energy ray curable resin or a cured product of a thermosetting resin.

3. 3. The laminate according to claim 1, further comprising a melt-extruded polyethylene layer or an adhesive layer at one or more selected from between the second resin layer and the substrate, between the substrate and the gas barrier resin layer, and between the gas barrier resin layer and the first resin layer.

4. The laminate according to any one of claims 1 to 3, wherein the polyethylene constituting the first resin layer and the polyethylene constituting the second resin layer are each independently at least one selected from low density polyethylene and linear low density polyethylene.

5. The laminate according to any one of claims 1 to 4, wherein the vapor-deposited film is a metal vapor-deposited film.

6. The laminate according to any one of claims 1 to 5, wherein the first resin layer and the second resin layer each independently have a thickness of 30 µm or more and 150 µm or less.

7. The laminate according to any one of claims 1 to 6, wherein the substrate has a thickness of 10 µm or more and 100 µm or less.

8. The laminate according to any one of claims 1 to 7, wherein the vapor-deposited film has a thickness of 1 nm or more and 150 nm or less.

9. The laminate according to any one of claims 1 to 8, wherein the gas barrier resin layer comprises a first polyethylene resin layer, a first adhesive layer, a layer containing a gas barrier resin, a second adhesive layer, and a second polyethylene resin layer.

10. The laminate according to claim 9 , wherein the layer containing the gas barrier resin has a thickness of 10 μm or more and 100 μm or less.

11. The laminate according to any one of claims 1 to 10, wherein the content of polyethylene in the entire laminate is 90 mass% or more.

12. The laminate according to any one of claims 1 to 11, which is for forming a body of a tube container body, the first resin layer being a sealant layer on an inner surface side of the body, and the second resin layer being a sealant layer on an outer surface side of the body.

13. The laminate according to claim 12 , wherein the printed layer and the printed protective layer are not formed in an area of ​​the second resin layer that is to be heat sealed to form a barrel portion of the tube container body.

14. A tube container body having a head and a body, The head portion includes a shoulder portion connected to one end of the body portion and a spout portion connected to the shoulder portion, and the body portion is formed of the laminate according to any one of claims 1 to 13. Tube container body.

15. The tube container body according to claim 14, wherein the head portion is made of a resin composition containing polyethylene.

16. A tube container body according to claim 14 or 15, Cap and A tube container comprising:

17. The tube container according to claim 16, wherein the cap is made of a resin composition containing polyethylene.

Citation Information

Patent Citations

  • Laminate tube container

    JP2006001602A

  • Laminate tube container

    JP2006282184A

  • Laminate tube container

    JP2014231372A

  • Tube container

    JP2018167860A

  • Laminate, packaging material, packaging bag and stand pouch

    JP2020157718A